Count - National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2011)
Learn to count from one to ten with the different animals.
OSLIS\Gale Nat Geo eBooks(2/2/23).
On board pages.
"The interactive Look & Learn series is designed to grow along with your child. A multi-layered skill-building approach introduces concepts with context reinforcement so learning sticks. These eye-catching books make early learning fun!"--Back cover.
"Developmental skill-building for ages one to four"--Back cover.
Description based on print version record.
Keywords: Counting -- Juvenile literature; Animals -- Juvenile literature; Counting; Animals; Electronic books- OSLIS; Board books; Electronic books